The practice of umbilical vessels catheterization in neonatal intensive care units: a survey - Shrestha, Nita; Khilfeh, Manhal; Dudani, Rajesh; Wu, Shou-Yien (International Journal of Contemporary Pediatrics, 2024)
Background: Umbilical venous catheterization and umbilical arterial catheterization provides easy access for administering fluids, exchange transfusion, medications, parenteral nutrition, blood pressure monitoring and blood sampling in neonates. Objective was to know the common practices related to the placement and maintenance of umbilical catheters, along with the associated complications in the level 3 and 4 neonatal intensive care units in the USA. Methods: A questionnaire-based survey study was conducted among NICU practitioners across United States. Only one survey was sent to each NICU. Results: Among the survey respondents, 50.8% represented level 3 NICUs, while 49.2% represented level 4 NICUs. The maximum duration for both UVC and UAC use was commonly reported as up to 7 days. Birth weight was the predominant method (86.8%) used for calculating catheter length. X-rays were universally employed for position confirmation. Heparin was widely utilized through UVC (96.7%), with a concentration of 0.5 IU/ml (73.7%). In cases of malpositioned UVC, practitioners employed techniques such as inserting another catheter, utilizing twisting movements during insertion, adjusting the UVC to a low position, and replacing the malpositioned UVC with a peripheral intravenous line. Common complications associated with UVC included line occlusion, thrombosis, and infections, while poor extremity perfusion and thrombosis were reported with UAC. Most units allowed feeding even when patients had a UAC in place. Conclusions: Despite the presence of institutional policies in most NICUs, practitioners encountered several complications during the use of umbilical catheters.